2014
DOI: 10.17129/botsci.42
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed bank, seed removal, and germination in a seasonally dry tropical forest in Veracruz, Mexico

Abstract: Abstract:The soil seed bank has a limited role in the seasonal dry tropical forest regeneration process, but seed removal and germination can also be limiting factors during the early forest recovery. In central Veracruz, Mexico, the soil seed bank was determined en fi ve fallows and two forests. Seed bank decreased from fallow to forest (1,303 to 101 seeds m -2 ); herbs and grasses predominated, thus the similarity between species composition of seed bank and vegetation was low. Seed removal and germination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…Their activity as predators and seed removers has a spatial effect, the magnitude of which varies depending on the group to which they belong (i.e., birds, insects or small mammals) (Hulme 1998). In order to evaluate seed removal by different groups of granivores, several studies have resorted to exclusion treatments, consisting in applying a mesh of different opening sizes according to the size of the granivores in question (Campos et al 2007, Álvarez-Aquino et al 2014, or a repellent, in the case of insects (Matamoros-Juárez & Gaitán-Martínez 2017, Bordones et al 2018). In temperate forests, birds, insects and rodents are efficient removers of pine seeds with different foraging strategies (Hulme & Kollmann 2005, Flores-Peredo et al 2011, Vander-Wall & Beck 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their activity as predators and seed removers has a spatial effect, the magnitude of which varies depending on the group to which they belong (i.e., birds, insects or small mammals) (Hulme 1998). In order to evaluate seed removal by different groups of granivores, several studies have resorted to exclusion treatments, consisting in applying a mesh of different opening sizes according to the size of the granivores in question (Campos et al 2007, Álvarez-Aquino et al 2014, or a repellent, in the case of insects (Matamoros-Juárez & Gaitán-Martínez 2017, Bordones et al 2018). In temperate forests, birds, insects and rodents are efficient removers of pine seeds with different foraging strategies (Hulme & Kollmann 2005, Flores-Peredo et al 2011, Vander-Wall & Beck 2012.…”
Section: Methodsmentioning
confidence: 99%
“…During July-September 2015 (rainy season) and January-March 2016 (dry season), four random granivore exclusion treatments with five repetitions each were conducted at each altitudinal tier (Arias-Le Claire 2001, Côté et al 2003, Flores-Peredo et al 2011. Treatments availed of meshes with different opening sizes to separate birds, rodents, and insects, and evaluate their respective contributions to seed removal (Hulme 1998, Hulme & Kollmann 2005, Álvarez-Aquino et al 2014, Magalhaes et al 2018. The experimental unit was a plastic Petri box with 20 seeds of P. hartwegii (n = 20).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding tree mortality, most of the research documents reported extreme microclimatic conditions as the main cause of the mortality of the tree species [34][35][36][37]. Lack of information on plant species performance under the harsh environmental conditions of degraded land explains why tree mortality is mentioned as an ecological limitation.…”
Section: Ecological Limitationsmentioning
confidence: 99%
“…La mayoría de las especies que habitan en los bosques tropicales caducifolios tienen semillas con latencia física (Baskin & Baskin 1998, Khurana & Singh 2001, lo que les permite formar reservorios de semillas (Álvarez-Aquino et al 2014, Soriano et al 2014. Una alternativa para eliminar esta condición en semillas de algunas especies es la escarificación física, química o la aplicación de agua caliente al promover que la testa u otras estructuras sean permeables al agua y aire, de tal modo que estimulen la germinación (Baskin & Baskin 1998, Khurana & Singh 2001.…”
Section: Introductionunclassified
“…Una alternativa para eliminar esta condición en semillas de algunas especies es la escarificación física, química o la aplicación de agua caliente al promover que la testa u otras estructuras sean permeables al agua y aire, de tal modo que estimulen la germinación (Baskin & Baskin 1998, Khurana & Singh 2001. La escarificación mecánica se ha utilizado mediante la fricción de la semilla con papel lija o corte de la testa con ayuda de navaja en distintas especies de leguminosas (Tigabu & Odén 2001, Álvarez-Aquino et al 2014, Bushman et al 2015. Los tratamientos pregerminativos químicos consisten en la inmersión de las semillas, por un periodo de tiempo, a sustancias corrosivas, entre ellas el ácido sulfúrico o ácido clorhídrico concentrado como se ha informado por distintos investigadores (Godínez-Álvarez & Flores-Martínez 1999, Baskin & Baskin 2004, Soriano et al 2014.…”
Section: Introductionunclassified